Animal Welfare Assessment System for Sustainable Cattle Production in Indonesia - Fathurahman, I; Maryam Jamilah, I (KnE Life Sciences, 2019)
The demand of a sustainable system to evaluate animal welfare in farming practices are now increasing. Indonesia as a developing country still have a problem in maintaining their animal welfare assessment system especially in cattle production. The lack of information and regulation about animal welfare in cattle farming practices affects the deprived animal welfare practices in the field. Poor animal welfare resulting in low efficacy of animal production. The quality of animal products is now judged in relation to the ethics of production including impact on the animal’s welfare, direct features, and consequences for consumers. In this paper, we suggest the concept of the animal welfare assessment system for sustainable cattle production in Indonesia which are based on protocols, human resources, and government. These three main elements in the animal welfare assessment system will be integrated to build a sustainable cattle production through better animal welfare practices. Enhanced animal welfare practice in cattle production chain will follow the sustainable production. We expect the implementation of this assessment system will give more value to the Indonesian cattle products in order to compete with international beef and dairy products. Keywords: Animal welfare, Cattle production, Assessment, System, Sustainable